E-moderating and E-tivities: The Implementation of a Workshop to Develop Online Teaching Skills in In-service Teachers - Jorge Eduardo Pineda Hoyos; Luis Hernando Tamayo Cano (Profile: Issues in Teachers' Professional Development)
This paper reports the experience of implementing a teacher’s professional development strategy that sought to foster e-moderator competencies among language faculty at a Colombian public university. The study aimed at finding the extent to which participants understood the concepts of e-moderation and e-tivities. We analyzed the participants’ performance in three different tasks to give account of the incorporation of the concepts. The results from the analysis of the tasks showed that participants understand online processes, they have some technical skills and they have many personal characteristics that will help them become e-moderators.